Language Prejudices of Cuban Youth Towards English - Pinto Pajares, Daniel (2018)
English is one of the most valuated language around the world. Valuations as global language or language of communication and its intrinsic supposed qualities to the language have organized a string of preconceptions that are not held from a linguistic point of view. However, they are latent prejudices which form a hegemonic space where English takes a principal role up. This research analyses the linguistic prejudices towards English presented by a sample of Cuban informants between 18 and 30 years old. Thus, the Cuban youth, as the social agent that is going to mark the course of Cuba in the coming decades, is the object of this sociolinguistic research. The fieldworkwas conducted in Havana and has a qualitative methodology that utilizes a semi-structured interview as the data collection tool.